Removal of Arsenic from Aqueous Solutions Using Zirconium Oxyhydrate Embedded Fe3O4 Nanoparticle - Wu, Shaolin; Hu, Wentao; Ma, Ming (Asian Journal of Chemistry, 2012)
A new type of magnetic nanoparticle Fe3O4@ZrO(OH)2 was prepared in Fe3O4 coated with zirconium oxyhydrate in order to remove high concentration toxic substances i.e., As(III/V) from aqueous solutions. This magnetic nanoparticle contained high attractive toward arsenic because zirconium oxyhydrate and excellent magnetic separability in the high-intensity magnetic field as well as good repeated for many times. The major effects on the removal of As(III/V), such as initial As(III/V) concentration, adsorption time, temperature, solution pH, co-existing anions, deabsorption and removal efficiency were investigated. The results clearly showed that the maximum adsorption capacity of Fe3O4@ZrO(OH)2 to As(III) and As(V) calculated by Langmuir equation were 188.68 and 108.70 mg/g, respectively. The adsorption time effect followed a pseudo-second-order rate equation, can get contact time to As(III/V) of 20 min to reach equilibrium. The enthalpy change (DHº) and entropy change (DSº) of As(III) were 17.38, 61.43 J/mol/K, which indicates the spontaneous nature of the As(III) adsorption process. The adsorption capacity of As(III) was increased from solution pH were 2-6 and decreased when pH were 9-12, while As(V) was always decreased along with the increase of solution pH. Interference ions have more effect As(III) than As(V). This magnetic nanoparticle could use more than four times after it was desorbed by NaOH. Besides, after using Fe3O4@ZrO(OH)2 as adsorbent to deal with an initial concentration of 10 mg/L of As(III) and 1 mg/L of As(V) solution, surplus concentration of arsenic less than 10 ppb. It is concluded that the magnetic nanoparticle Fe3O4@ZrO(OH)2 can be considered as a good settlement performance, high arsenic uptake capability and fine utilization make it potentially excellent and attractive material for arsenic removal in future.